Dynamics of morphofunctional parameters young women in the process of correction overweight - Ovdii M.A. (Морфологія, 2013)
Background. Currently, much attention is paid to the problem of correction and prevention overweight and obesity in young people using different methods of physical activity, however, the use of the walking with breathing exercises presented in the literature is not enough. Objective. The present study investigated the dynamic of morphological and functional indicators in young women with overweight under the influence of the walking with breathing exercises. Methods. 23 young women (21-25 years) participated in the present study and performed walking with breathing exercises four times per week for 12 weeks. Before and after the intervention, measurements of weight, body mass index, waist, abdomen and hips circumferences, body composition, and functional parameters. Results. After 12 weeks found a positive trend in anthropometric and functional parameters, reduced body weight by 8,7% (p<0,01), body fat by 6,9% (р <0,01), waist and abdomen circumferences by 8,2 % and 6,9% (р<0,01р<0,05 respectively), increased lung capacity by 15,7% (<0,01), adaptation of the cardiovascular system to the conditions of hypoxia and other functional parameters. Conclusion. The present study suggests that walking with breathing exercises improves the morphofunctional parameters overweight young women.